EXPLORING LEADERSHIP STYLE ON EMPLOYEE COMPETENCE: AUTHENTIC AND SERVANT LEADERSHIP ON WORKABILITY - Ester Manik; Iwan Sidharta; Tini Supartini (STMIK Mardira Indonesia, Bandung, 2022)
The workability of an employee in a company or organization has an essential role in achieving organizational goals. Therefore, various efforts need to increase the workability of employees to an optimal level. One effort that needs improvement is to determine the ideal leadership style according to the characteristics of employees so that they are more optimal in carrying out their duties and responsibilities so that their abilities are maxim. Authentic leadership and servant leadership styles can significantly change employee work abilities. In this study, the respondents were all field employees in one of the electricity generation sectors, totaling 566 employees. The analytical method used is a different pair t-test with this test, which aims to see how the changes made by the two leadership styles improve employee performance. Keywords: authentic leadership style, servant leadership style, workability.